(untitled) (Journal of Dhaka Medical College, 2015)
Endometriosis, defined as the presence of endometrial tissue outside the uterus, is a challenging condition associated with substantial morbidity. Theories on the cause of the disease include retrograde menstruation, coelomic metaplasia, altered immunity, stem cells, and genetics. Management of endometriosis must be individualized according to the desired treatment outcome, whether it is relief of pain, improvement of fertility, or the prevention of recurrence. For alleviation of endometriosis-associated pain, medical treatment is generally successful, with no medical agent being more efficacious than another in spite of significantly differing side-effect profiles. Surgical therapy has also been demonstrated to reduce pain scores in comparison with expectant management, although conservative surgery has been frequently associated with recurrence. Endometriois has been associated with infertility; however, the mechanisms by which it affects fertility are still not fully understood. For treatment of endometriosis-associated infertility, suppressive medical treatment has been proven to be detrimental to fertility and should be discouraged, while surgery is probably efficacious for all stages. Controlled ovarian hyperstimulation with intrauterine insemination is recommended in early-stage and surgically corrected endometriosis. Combined surgery with Gonadotropin-releasing hormone (GnRH) analog treatment has been proposed to be first-line therapy, followed by in vitro fertilization (IVF) as second-line therapy in advanced cases. This article reviews the proposed mechanisms of endometriosis pathogenesis, its current management strategies and its effects on fertility, and treatments of endometriosis-associated infertility. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 245-255